Meat products handbook : practical science and technology - Feiner, Gerhard, ....- (Cambridge : Woodhead, 2006)
Based on over 20 years of experience, Meat Products Handbookis a comprehensive one-volume reference on the main types of meat products and their methods of manufacture. It combines a detailed practical knowledge of processing and ingredients with the scientific underpinning to understand the effect of particular process steps and ingredients on product safety and quality. The first part of the book reviews meat composition and its effect on quality together with the role of additives. There are chapters on fat, protein and other components in meat, changes in meat pre- and post-slaughter, and additives such as phosphates, salts, hydrocolloids, proteins, carbohydrates and fillers. Part two reviews raw materials, additives, manufacturing processes and representative recipes from around the world for a range of particular meat products. It includes chapters on cooked ham and bacon, cooked, fresh and raw fermented sausages, raw fermented and non-fermented salami, cured air-dried products, burgers and patties, brawn and meat jelly, canned and marinated meat. The final part of the book discusses quality and safety issues, particularly meat microbiology.